Предмет: Алгебра,
автор: викториявернер
6/х-1-6/х=2 помогите решить уравнение
Ответы
Автор ответа:
0
6/х-1 - 6/х =2 (умножаем все на х^2-1)
6х/х^2-х - 6х-6/х^2-х = 2х^2-2/х^2-1 (делим всё на х^2-1)
6х-6х+6 =2х^2-2
6 =2х^2-2
0=2х^2-2-6
0=2х^2-8
8/2=х^2
4=х^2
Х= +-2
Ответ:+-2
6х/х^2-х - 6х-6/х^2-х = 2х^2-2/х^2-1 (делим всё на х^2-1)
6х-6х+6 =2х^2-2
6 =2х^2-2
0=2х^2-2-6
0=2х^2-8
8/2=х^2
4=х^2
Х= +-2
Ответ:+-2
Похожие вопросы
Предмет: Геометрия,
автор: irinagarabazi807
Предмет: Биология,
автор: vovaermoshkin98
Предмет: Математика,
автор: ni1628252
Предмет: Математика,
автор: катерина168
Предмет: Математика,
автор: nikitagest